Pengembangan Gim Edukasi Pembelajaran Kata Benda dan Kata Kerja Bahasa Inggris pada Tingkat Sekolah Dasar - Ervian, Jenrico; Dirgantara, Harya Bima (Research and Community Service UNIVERSITAS KALBIS, 2024)
The purpose of this research is to develop an educational game that help elementary school children learn English vocabulary. The materials applied to the game are limited to nouns and verbs with matching card game types. The method used is Game Development Life Cycle (GDLC) with five stages: initiation, pre-production, production, game testing, beta testing, and release. The programming languages used are HTML, CSS, and Javascript. The final result of this research is an educational game